Influence of flow rate in the mean and fluctuating pressures of a stilling basin - N. Figueiredo (2014)
The present work concerns the experimental study of the energy dissipation downstream of aconverging stepped spillway equipped with a ski jump bucket. Experimental tests have beenperformed in order to define flow discharges jet trajectories, mean pressures and pressurefluctuations at the channel bottom, for different conditions (flow rates and tail water levels).The application of laboratory techniques, such as the imaging capture technique applied to thestudy of the trajectory of jets and the measurement of pressure fluctuations with piezoelectricprobes will be described.